Development of 2D Home Safety Animation Applications for Primary School Students with Learning Disability ADHD - Hamid, Hashima; Mahazir, Nur Syamimee; Madar, Ahmad Rizal; Tien , EEE Chinge (Research and Innovation in Technical and Vocational Education and Training, 2021)
This article abstract discusses the work of 2-dimensional (2D) animation about how to keep home safe for the children with ADHD. This 2D home safety animation was developed because according to this study, ADHD has difficulty concentrating and this children constantly running, climbing and jumping no matter the time and place. Attention Deficit Hyperactivity Disorder (ADHD) is one of the learning disabilities. The methodology used in the application development is the ADDIE Model which has 5 phases namely analysis phase, design phase, development phase, implementation phase and evaluation phase. The analysis was based on interviews with Special Education teachers at Sri Gading Primary School, Batu Pahat and the developers using the expert check form method as the instrument of this study. The findings from the experts are positive and overall this app is a great medium for learning about home safety so that accidents can be avoided in the future.